Pendampingan Membaca Al-Qur’an Dengan Ilmu Tajwid Di Majelis Ta'lim Nur Hidayah Desa Cogreg - Sofwani, Muhammad; Solid, Muhammad; Basith, Yudril (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Tajweed science is a very important knowledge to have for a child from an early age so that he can recite properly and correctly in accordance with the rules of tajweed science. However, in Cogrek Village, Ciseeng District, Bogor Regency, children still lack the correct application of tajweed in reading the Qur'an. This service activity aims to teach how to read the Qur'an well and correctly with the science of tajweed to children at the Ta'lim Nur Hidayah Assembly, Cogrek Village, Ciseeng District. The method used in this activity is a lecture, where children are given an understanding of the science of tajweed in learning to read the Qur'an. This activity will be carried out from the end of Maghrib until Isha on June 28, 2024. Based on the results of the assessment, there was a significant increase in the understanding of tajweed, especially in Mad law, in children who recited at the Ta'lim Nur Hidayah Assembly. This increase was seen by comparing the children's abilities at the week of.